Pseudolinear C4d deposits in a hereditary glomerulopathy caused by a rare NC1 collagen-4-alpha-5 missense mutation: a "new disease entity"?. (3rd September 2019) - Roy, Sanjeet; Nalwa, Aasma; Keith, Jared; Weck, Karen; Singh, Harsharan; Nickeleit, Volker
ABSTRACT: C4d positive glomerulopathies with pseudolinear capillary wall deposits caused by basement membrane (GBM) remodeling have sporadically been reported in renal transplants. Here we describe the case of a hypertensive 60 year-old male with a 5 month history of nephrotic range proteinuria in the setting of normal serum creatinine, complement and ANA levels. Work-up showed MGUS (IgG/kappa restricted). A diagnostic renal biopsy to search for monoclonal gammopathy of renal significance demonstrated thickened glomerular capillary walls with strong pseudolinear complement factor C4d deposits by immunofluorescence microscopy (IF); all other IF studies including stains for Col4A3 were unrevealing with only minor abnormalities seen for Col4A5 . The strong and unusual C4d staining of undetermined direct diagnostic significance triggered additional electron microscopic studies uncovering marked structural GBM changes suggestive of a hereditary nephropathy. Further genetic testing revealed a very rare X-linked single missense mutation in the NC1 domain of Col4A5 (exon 51) with a single amino acid substitution ( COL4A5 p.A1581S) that has thus far not been reported in hereditary nephropathies. Our case provides further support for pseudolinear glomerular C4d deposits as general markers of GBM remodeling, in our case an unexpected hereditary nephropathy in an older male. Pseudolinear C4d: a general signpost for architectural GBM disturbance and a stimulus for in-depth studies including electron microscopy.